Iowa Birdline update, December 24, 1990 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for December 24, 1990. Highlights include reports from some of the Christmas bird counts. Includes notes in preparation for next week's update. Epson - sheet feed/flatbed